Occurrence, chemistry and genesis of the nickel-rich phases in the ultramafic rocks from Swat, northwestern Pakistan - Arif, Mohammad; Moon, C.J. (Journal of Himalayan Earth Sciences, 1994)
Trace amounts of finely disseminated Ni-rich phases, including heazlewoodite, pentlandite, millerite, godlevskite, violarite and awaruite, occur in the variably serpentinized ultramafic rocks of the Swat valley. The mode of occurrence, textural relationships with each other and with the associated silicate and oxide phases, relative modal abundance and chemical variation; all indicate that only the pentlandite represents the original sulphide phase. The rest are derived from pentlandite by the process of alteration. The additional amount of Ni, required for the conversion of pentlandite to heazlewoodite and other Ni-richer phases, was possibly derived by the serpentinization of primary olivine.